PHYTOCHEMICAL ANALYSIS AND DETERMINATION OF ANTIBACTERIAL AND ANTICANCER ACTIVITIES OF SUAEDA MONOICA - SWATHI MINUMULA SUDARSHAN; SATHVIKA CHINTALAPANI; MANGAMOORI LAKSHMI NARASU (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the study is to screen the whole plant extract of Suaeda monoica for its phytochemicals, determine its antibacterial and anticancer activities by sulforhodamine B (SRB) assay. Methods: The powdered form of S. monoica with different solvents (ethanol, methanol, acetone, and diethyl ether) was used to screen its phytochemicals. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were performed using microdilution methods. Based on the results of MIC, the lowest concentration of antibacterial agent was subcultured on agar plates for MBC values. The zone of inhibition was determined using agar well diffusion method. The percentage of cell-growth inhibition for breast cancer cell line (MDAMB-231) was studied using SRB assay. Results: The analysis revealed the presence of varied classes of phytochemicals except for acidic compounds with ethanol extract showing maximum compounds. All the extracts showed effective antibacterial activity against tested pathogens with MIC, MBC values ranging from 0.0156 to 0.625 mg/ml and 2.5 to 10 mg/ml, respectively. A significant zone of inhibition was observed with diethyl ether extract against Staphylococcus epidermis. The lowest concentration that showed 50% cell growth inhibition against MDAMB-231 was that of diethyl ether extract (60.18 μg/ml). Conclusion: The present study depicts S. monoica as a natural source of bioactive compounds with significant antibacterial and anticancer activities. Further studies concerning the separation and isolation of the compounds are required.